2014
DOI: 10.1038/bmt.2014.13
|View full text |Cite
|
Sign up to set email alerts
|

Second cancer risk in adults receiving autologous haematopoietic SCT for cancer: a population-based cohort study

Abstract: , CM Vajdic 5 and CAST study group 6 Population-based evidence on second cancer risk following autologous haematopoietic SCT (HCT) is lacking. We quantified second cancer risk for a national, population-based cohort of adult Australians receiving autologous HCT for cancer and notified to the Australasian Bone Marrow Transplant Recipient Registry 1992Registry -2007. Cancer diagnoses and deaths were ascertained by linkage with the Australian Cancer Database and National Death Index. Standardized incidence ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 40 publications
5
22
2
Order By: Relevance
“…While this Australian study reported excess risk for MM after autologous HSCT, 14 we observed no evidence of increased MM risk in our cohort. In the Australian study, however, TBI was part of the conditioning regimen for some of the autologous HSCT recipients, with patients undergoing the TBIbased regimen less frequently in recent years.…”
Section: Discussioncontrasting
confidence: 80%
“…While this Australian study reported excess risk for MM after autologous HSCT, 14 we observed no evidence of increased MM risk in our cohort. In the Australian study, however, TBI was part of the conditioning regimen for some of the autologous HSCT recipients, with patients undergoing the TBIbased regimen less frequently in recent years.…”
Section: Discussioncontrasting
confidence: 80%
“…A report restricted to autologous HCT demonstrated a SIR of 2.55 for melanoma, and multivariate analysis revealed age ⩾ 45 years, male patients and relapse following HCT as risk factors for melanoma development. 19 …”
Section: Methodsmentioning
confidence: 99%
“…The cumulative incidence is 1%–6% at ten years after HCT, and continues to rise over time without a plateau. 139142 The most common sites include oral cavity, skin, breast and thyroid, but rates are also elevated in esophagus, liver, nervous system, bone and connective tissues compared with the general population. 143 Myeloablative TBI, young age at HCT, chronic GvHD and prolonged immunosuppressive medications beyond two years are well-documented risk factors for many types of cancers.…”
Section: Introductionmentioning
confidence: 99%